PENGARUH CORPORATE REPUTATIONTERHADAP RECOMMENDATIONMELALUI MEDIASI PERCEIVED VALUE, MODERASI TOUR LEADER PERFORMANCE DANFLOW EXPERIENCE PADA PT AL-MADINAH CITRA INTERNASIONAL DI SURABAYA - Maharani Nur Kartikasari; Indarini Indarini; Siti Rahayu (CALYPTRA, 2018)
This study aims to examine the effect of Corporate Reputation on Recommendation, the influence of Functional Value on Recommendation, the influence of mediation from functional and emotional value variables that can mediate the relationship between corporate reputation and recommendation. And the influence of tour leader performance moderation on the relationship between corporate reputation, perceived value, and recommendation at PT Al-Madinah Citra InternasionalinSurabaya. This study used a sample of 160 respondents. This research uses quantitative approach through statistical test. The test is done by using SEM (Structural Equation Modeling) through AMOS software version 22.0 (Analysis of Moment Structures) to test the measurement and structural model. The results of this study indicate that Corporate Reputation proved to have a positive effect on the Recommendation at PT Al-Madinah Citra International in Surabaya. Functional Value proved to have a positive effect on Emotional Value at PT Al-Madinah Citra Internasional in Surabaya. Functional Value is not proven to mediate the relationship between Corporate Reputation and Recommendation at PT Al-Madinah Citra Internasional in Surabaya. Emotional Value proved to mediate the relationship between Corporate Reputation and Recommendation at PT Al-Madinah Citra International in Surabaya. And Tour Leader Performance is not proven to moderate the relationship between Corporate Reputation, Perceived Value, and Recommendation at PT Al-Madinah Citra Internasional in Surabaya.